Community of the believers as a witness to the world - Chikakuda, Wallace Ezara (My University, 1991)
Refer to document
Thesis (M.Theology) -- University of Limpopo, 1991
Keywords: Community of believers; Old Testament; Beards - Religious aspects - Old Believers; Religious adherents